Reverse electrical remodeling following pressure unloading in a rat model of hypertension-induced left ventricular myocardial hypertrophy - Ruppert, Mihály; Korkmaz-İçöz, Sevil; Li, Shiliang; Karck, Matthias; Radovits, Tamás; Szabó, Gábor (Hypertension research, 2017)
Pressure overload-induced left ventricular myocardial hypertrophy (LVH) is characterized by increased proarrhythmic vulnerability. In contrast, pressure unloading leads to reverse remodeling and decreases LVH-associated arrhythmogenicity. However, cellular changes that occur during reverse electrical remodeling have been studied less. Therefore, we aimed to provide an electrocardiographic characterization of a rat model of LVH that underwent pressure unloading and to simultaneously identify the underlying cellular and functional alterations. LVH was induced in rats by abdominal aortic banding for 6 or 12 weeks. Sham-operated animals served as controls. Pressure unloading was evoked by removing the aortic constriction after week 6 (debanded). Serial echocardiography and electrocardiography were performed to investigate the development and the regression of LVH. Protein expression levels were detected by western blot. Myocardial fibrosis was assessed by Picrosirius red staining. Pressure unloading resulted in the regression of LVH in correlation with the reversion of the prolonged corrected QT interval (cQT: 68.7±1.6 vs. 91.0±1.9 ms debanded week 12 vs. AB week 12, P<0.05). Furthermore, pressure unloading prevented the functional decompensation of LVH and simultaneously preserved adequate atrioventricular conduction (PQ: 47.5±1.2 vs. 53.8±1.9 ms debanded week 12 vs. AB week 12, P<0.05). Finally, pressure unloading effectively preceded the broadening of the QRS complex (QRS: 21.8±0.5 vs. 24.9±0.7 ms debanded week 12 vs. AB week 12, P<0.05) in parallel with the attenuation of interstitial collagen accumulation. The regression of LVH with maintained cardiac function and decreased myocardial fibrosis contributes to pressure unloading-induced reverse electrical remodeling.